#Urogyn: What's Trending on Instagram? A Cross-sectional Observational Study. Issue 5 (May 2020) - Qin, Lei Alexander; El-Neemany, Diana; Winkler, Harvey; Shalom, Dara
Abstract : Objective: The aim of the study was to identify the prevalence, authorship, and type of information pertaining to topics in urogynecology on Instagram via hashtag and content analysis. Methods: A list of 20 hashtags consisting of common urogynecologic diagnoses, procedures, and lay terms was derived from the American Urogynecologic Society's "Patient Fact Sheets." The top 9 and most recent 30 posts for each hashtag were reviewed for authorship and content type. Content type was divided into the following categories: educational; tagged but unrelated posts; pertinent patient experiences; community building and outreach; advertisements; and humor. Searches were limited to English language posts. Results: Our search yielded 561, 133 posts. The 5 most popular hashtags were pelvic floor (30.6%, n = 171, 855), interstitial cystitis (12.8%, n = 71, 977), pelvic pain (10.0%, n = 56, 505), incontinence (9.3%, n = 52, 169), and prolapse (3.9%, n = 21, 839). The authorship of the top 9 and most recent 30 posts (n = 537) were as follows: patients (34.6%, n = 186), allied health professionals (29.2%, n = 157), physicians (13.4%, n = 72), and other (22.7%, n = 122). Further authorship and content analysis revealed that allied health professionals authored the most informational posts (45.6%, n = 129) and patients authored the most unrelated (69.4%, n = 43), patient experience (81.7%, n = 125), community building (55.8%, n = 53), and humorous posts (38.5%, n = 10). Conclusions: More than 500, 000 posts related to urogynecology were identified on Instagram. Most posts were authored by patients and allied health professionals with a small contribution from physicians. Greater physician participation may increase the quantity of educational posts and offer a low-cost platform for networking and connecting with patients and other providers. Abstract : Supplemental digital content is available in the text.